Inclusive education and teacher training: what do students say? (Revista Internacional de Formação de Professores, 2021)
The measures of inclusive education and curricular flexibility are presented as ways to deepen the democratic school in a context of managerialism in the approach to the administration of the educational system and point to integrated knowledge management and multilevel intervention. The study, of an exploratory nature, aims to understand how they influence initial training, using students' listening. The data collected point to the widespread receptivity of the idea of School for All, an unclear distinction between homogenization and differentiation of the teaching-learning process, and tension between a culture of obedience to the prescribed guidelines and the perspective of autonomous teachers as curricular managers.
Keywords: Inclusive Education. Curricular Flexibility. Teacher Socialization. Initial Training.